Impact of Tunisian clay nanofillers on structure and properties of post-consumer polypropylene-based nanocomposites. (September 2019) - Zdiri, K; Elamri, A; Hamdaoui, M; Khenoussi, N; Harzallah, O; Brendle, J
This study investigates the influence of clay nanofiller on morphological, thermal, and mechanical behaviors of post-consumer polypropylene (PCPP)-based nanocomposites. Waste polypropylene was mixed with 1%, 3%, 5%, and 7% of Tunisian clay nanoparticles using twin-screw extruder. The structure and morphology of raw, purified, and organo-modified clays were characterized by Fourier-transform infrared spectroscopy and X-ray diffraction (XRD). The influence of clay nanoparticles content on the thermal behavior of waste polypropylene was studied by means of thermogravimetric analysis. The effect of nanoclay on morphology and properties of PCPP/clay nanocomposites was also studied. It was found from transmission electron microscopy and XRD analysis that clay nanoparticles are well dispersed into PCPP matrix and the addition of organo-modified Tunisian clay did not change the crystal structure of the PCPP polymer. Thus, organically modified Tunisian clay can be used for preparing organic–inorganic hybrids by melt processing with waste PP polymers. In dead, by varying the nanofiller loading, mechanical properties (Young's modulus, tensile strength, and elongation at break) and thermal stability of filled PCPP showed an increase as compared to unfilled polymer. Optimal mechanical performances were obtained with 5% clay loading.